Application of the monitoring and early warning system for internal solitary waves: Take the second natural gas hydrates production test in the South China Sea as an example - Dan-yi Su; Bin-bin Guo; Qian-yong Liang; Chu-jin Liang; Fei-long Lin; Su-meng Jiang; Yi-fei Dong; Xue-min Wu (China Geology)
Internal solitary waves (ISWs) contain great energy and have the characteristics of emergency and concealment. To avoid their damage to offshore engineering, a new generation of monitoring and early warning system for ISWs was developed using technologies of double buoys monitoring, intelligent real-time data transmission, and automatic software identification. The system was applied to the second natural gas hydrates (NGHs) production test in the Shenhu Area, South China Sea (SCS) and successfully provided the early warning of ISWs for 173 days (from October 2019 to April 2020). The abrupt changes in the thrust force of the drilling platform under the attack of ISWs were consistent with the early warning information, proving the reliability of this system. A total of 93 ISWs were detected around the drilling platform. Most of them occurred during the spring tides in October–December 2019 and April 2020, while few of them occurred in winter. As suggested by the theoretical model, the full-depth structure of ISWs was a typical current profile of mode-1, and the velocities of wave-induced currents can reach 80 cm/s and 30 cm/s, respectively, in the upper ocean and near the seabed. The ISWs may be primarily generated from the interactions between the topography and semidiurnal tides in the Luzon Strait, and then propagate westward to the drilling platform. This study could serve as an important reference for the early warning of ISWs for offshore engineering construction in the future.©2023 China Geology Editorial Office.